Successful deployment of marker assisted selection (MAS) for inbred and hybrid development in long-day onion (Allium cepa L.) - Saini, Navinder; Hedau, Nirmal K.; Khar, Anil; Yadav, Shailendra; Bhatt, Jagadish C.; Agrawal, Pawan K. (The Indian Journal of Genetics and Plant Breeding, 2016)
In the present investigation, male sterile and maintainer lines were identified using molecular markers in three long day onion populations. Molecular markers, 5’cob and orfA501 were able to distinguish effectively normal (N) and sterile (S) cytoplasm in all the three populations. The observed frequency of S cytoplasm inVL Piaz 67 (100%),VL Piaz3 (86.4%) and KR1 (90%) was higher than N cytoplasm. Out of the two PCR markers viz., OPT and PsaO used to determine the nuclear fertility restorer locus (Ms locus), OPT was found better than PsaO. Increased frequency of dominant homozygous alleles (87.4%) followed by heterozygous alleles (8.6%) and homozygous recessive alleles (4.0%) was observed. Fertility/sterility of plants were validated by acetocarmine staining of the pollens and correlated with observations made using molecular markers. Out of the three populations studied, only 12 plants (2.15%) happened to be completely male sterile in VL Piaz-3 and KR1 population, whereas there was no male sterile plant observed among the population inVL Piaz 67. Selfing and test crossing of plants having normal (N) cytoplasm led to the development and identification of maintainer lines in VL Piaz3 and KR1 population. This is the first example of deploying DNA markers for identification and purification of male sterility and hybrid development in long day onion in Indian population.